Corneal collagen cross-linking by sun exposure and high dose oral riboflavin: a multicentric longitudinal observational study - Edna Motta Almodin; Flávia Almodin; Juliana Almodin (Revista Brasileira de Oftalmologia, 2025)
ABSTRACT Objective: To evaluate the efficacy of high-dose oral riboflavin treatment combined with sun exposure in preventing the progression of keratoconus. Methods: A retrospective, multicenter observational study involving 53 keratoconus patients (106 eyes) from three Brazilian cities. Patients were instructed to take 400 mg/day of oral riboflavin and to sunbathe for 30 minutes daily, in addition to avoiding eye rubbing. Keratometric measurements were evaluated before and after 6, 12, 24, and 36 months of treatment. Results: After 6 months, 42 patients remained in the study. Corneal flattening was observed without significant decrease in thickness. At 36 months, stabilization of keratoconus was noted, with minor variations in astigmatism and corneal thickness measurements. Conclusion: Oral riboflavin treatment combined with sun exposure appears to be effective in stabilizing the progression of keratoconus.